2021
DOI: 10.3390/ijms23010136
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals Synergistically Promote Osteogenesis in Cultured 7F2 Osteoblasts and Mitigate Inhibition of Differentiation and Maturation in Simulated Microgravity

Abstract: Microgravity is known to impact bone health, similar to mechanical unloading on Earth. In the absence of countermeasures, bone formation and mineral deposition are strongly inhibited in Space. There is an unmet need to identify nutritional countermeasures. Curcumin and carnosic acid are phytonutrients with anticancer, anti-inflammatory, and antioxidative effects and may exhibit osteogenic properties. Zinc is a trace element essential for bone formation. We hypothesized that these nutraceuticals could counterac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Antioxidants (AO) only showed a positive effect on BL in animal and cell studies [ 72 , 75 ], but not in human studies [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants (AO) only showed a positive effect on BL in animal and cell studies [ 72 , 75 ], but not in human studies [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Application of AO had an effect in studies on cells and animals. Both nutraceuticals and polyphenols have an elevating effect on ALP activity in OBs exposed to s-µ g [ 72 , 75 ]. The reduced BL in rats could be due to alleviation of the µ g -induced inhibition of Wnt/β-catenin pathway, which enhances BF, because ALP, N-terminal propeptide of type 1 procollagen, and β-catenin are increased [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that nutraceuticals curcumin and carnosic acid synergistically promoted osteogenesis in cultured murine 7F2 osteoblast cells and alleviated microgravity-induced inhibition of osteogenic differentiation and function. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of ROS may further block the osteoblast activities and their differentiation followed by low intensity of mineralization and minimal osteogenesis [55,56]. However, antioxidants have a paradoxical effect, as they help in differentiation of osteoblasts followed by formation of bone [31,[57][58][59], maintain osteocytes required for osteogenesis, while simultaneously they minimise the osteoclast activities and their differentiation. Osteoclast and osteoblast activities are regulated by various factors which are produced by osteoblasts themselves and also by osteocytes for the bone remodelling such as receptor activator of NF-κB ligand (RANKL) and osteoprotegerin (OPG).…”
Section: Ros In Bone Remodellingmentioning
confidence: 99%
“…These antioxidants are not only direct scavengers of ROS but also maintain significant levels of GSH for the conjugation with GSH reductase. Thus, they can eliminate GSSG and can sustain the standard GSH/GSSG levels thereby balancing the intracellular redox state [32,57,59]. Consequences of antioxidants on bone metabolism have been reported, suggesting the low levels of antioxidants presented in plasma of aged or osteoporotic animals [77].…”
Section: Antioxidants In Bone Remodelling and In Bone Lossmentioning
confidence: 99%